Titanium‐Based MOF Materials: From Crystal Engineering to Photocatalysis. Issue 12 (13th September 2020) - Li, Lan; Wang, Xu‐Sheng; Liu, Tian‐Fu; Ye, Jinhua
Abstract: Titanium (Ti)‐based metal–organic frameworks (MOFs) have attracted intensive attention due to the low toxicity, high earth's crust abundance, and unique photocatalytic properties of Ti elements. Great efforts have been devoted to the synthesis of novel architectures and their potential applications involving photocatalysis. However, Ti‐MOFs are still very scarce owing to their challenges in controlling the Ti chemistry in the reaction system. Until now, some significant results have been achieved, which may shed new insight into the future investigation of Ti‐MOFs. Herein, some representative researches in Ti‐MOFs are summarized and reviewed from the following four aspects: first, various synthetic strategies for preparing Ti‐MOFs are introduced; second, diverse structures containing multi‐connected ligands are presented in detail; third, the potential photocatalytic applications of Ti‐based MOFs involving H2 production, CO2 reduction, H2 O2 production, N2 fixation, remediation of organic and inorganic pollutants, as well as organic transformation reaction and photocatalytic sensors are discussed; finally, perspectives on current challenges and emerging opportunities in this research field are discussed. Through summarizing this specific type of MOF, this review is expected to stimulate researchers' interest for in‐depth investigation of novel structures synthesis, as well as new applications and concepts in these intriguing fields. Abstract : Titanium‐based metal–organic frameworks (MOFs) have been demonstrated as an ideal platform for photocatalytic applications. Herein, synthetic and design strategies and the status on this topic are comprehensively reviewed, aiming to promote the discovery and development of advanced MOF materials and their applications in various fields.